Influential factors for technology-enhanced learning: professionals - Schweighofer, Patrick; Weitlaner, Doris; Ebner, Martin; Rothe, Hannes (Journal of Research in Innovative Teaching & Learning, 2019)
Purpose The purpose of this paper is to include several studies that define different critical success factors (CSF) which have to be considered to support the implementation of technology-enhanced learning (TEL) approaches. An analysis of such studies revealed that regional differences seem to determine the CSF for TEL approaches, certain CSF are relevant for TEL approaches in general and professionals in higher education determine which influential factors they consider when implementing TEL approaches. Thus, the question arises: in general, which influential factors do professionals in Austrian and German institutions of higher education actually consider when implementing TEL approaches? Design/methodology/approach The study is a quantitative research approach based on survey data. Findings The results show that certain influential factors seem to be generally important, such as the factors of respecting learning success or motivation. However, the outcome of the study also indicated that different mo...
Keywords: Importance of influential factors; Influential factors; Moderating effects of influential factors; Opinion of professionals in higher education; Technology-enhanced learning; Time exposure for influential factors